High levels of hybridization between molecular forms of Anopheles gambiae from Guinea Bissau - Oliveira, E.; salgueiro, P.; Palsson, K.; Vicente, J.L.; Arez, A.P.; Jaenson, T.G.; Caccone, A.; João Pinto (Journal of Medical Entomology, 2008)
In the malaria vector Anopheles gambiae Giles sensu stricto, two molecular forms denoted M and S are considered units of incipient speciation within this species. Very low hybrid frequencies and significant genetic differentiation have been found in sympatric M- and S-form populations. We studied the molecular form composition and the degree of genetic differentiation at 15 microsatellites in two samples of An. gambiae collected in two consecutive years from Bissau, Guinea Bissau. High frequencies of M/S hybrids (19–24%) were found in this area. Coincidently, very low levels of genetic differentiation were detected between forms when analysis involved microsatellites mapped at chromosome-3 (mean Fst, 0.000–0.002). The single exception was the X-linked AGXH678, for which high differentiation was measured (Fst, 0.158–0.301). This locus maps near the centromere of chromosome X, a low recombination region in which selection is likely to promote divergence between M and S forms. These results strongly suggest that the degree of isolation between M and S forms, considered the units of incipient speciation within An. gambiae, is not homogenous throughout the species distribution range.